Electrophotographic belt and electrophotographic image forming apparatus
By using specific compound 1 and perfluoropolyether in the surface layer of the electrophotographic tape, the problem of degradation of surface cleaning performance of the electrophotographic tape in the prior art is solved, and environmentally friendly high-cleaning performance and high-quality image formation are achieved.
Patent Information
- Application Number
- CN202210424060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2022-04-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-04-21
AI Technical Summary
The existing electrophotographic tape has excellent degradability in the natural environment, but its surface cleaning performance is reduced during use, resulting in a decrease in toner mold release.
The surface layer consisting of Compound 1, perfluoropolyether and binder resin represented by the structural formula (I) and Structural formula (II), the perfluoropolyether is better dispersed in the binder resin through the graft copolymer of Compound 1 to improve the surface cleaning performance.
The environmentally friendly electrophotographic tape is realized, which can maintain the surface cleaning performance for a long time and stably form high-quality electrophotographic images.
Smart Images

Figure CN115236958B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrophotographic belt used in an electrophotographic image forming apparatus such as a copying machine or a printer, and an electrophotographic image forming apparatus including the electrophotographic belt. Background Art
[0002] In an electrophotographic image forming apparatus capable of forming a full-color image, a tandem system has been widely adopted in which toner images of each color of yellow, magenta, cyan, and black (YMCK) are superimposed on an intermediate transfer belt and then collectively transferred to paper to obtain a full-color image. As an intermediate transfer belt used in this case, there is a known electrophotographic belt including, for example, a base layer having carbon black dispersed in a binder resin such as polyimide or polyetheretherketone.
[0003] With the demand for further improvement of the image quality of electrophotographic images, there is a demand for further improvement of the secondary transfer properties of toners in intermediate transfer belts. In order to improve the secondary transfer performance of intermediate transfer belts, it is proposed to introduce perfluoropolyether into the surface layer of the toner bearing surface (hereinafter sometimes referred to as "surface") of the intermediate transfer belt to improve the toner release property of the surface.
[0004] In addition, in Japanese Patent Application Laid-Open No. 2019-12265, an electrophotographic tape is disclosed, which includes a surface layer having a perfluoropolyether dispersed in a binder resin by a comb-shaped graft copolymer. The comb-shaped graft copolymer has a specific molecular weight and is a copolymerization product of a (meth)acrylate having a fluoroalkyl group and a methacrylate macromonomer having polymethyl methacrylate in a side chain. It is disclosed that the use of such a comb-shaped graft copolymer allows the perfluoropolyether to be better dispersed in the binder resin.
[0005] The inventors have found that the comb-shaped graft copolymer according to Japanese Patent Application Laid-Open No. 2019-12265 is excellent in the dispersibility of perfluoropolyether. In view of this, the inventors have studied setting the number of continuous carbon atoms bonded to fluorine atoms in the comb-shaped graft copolymer to 3 or less. Specifically, the introduction of oxygen atoms into the carbon chain used as the main chain of the perfluoroalkyl group and the setting of the number of continuous carbon atoms bonded to fluorine atoms to 3 or less were studied. It is believed that the organic fluorine compound in which the number of continuous carbon atoms bonded to fluorine atoms is set to 3 or less has excellent degradability in the natural environment and therefore hardly remains in the environment. Therefore, the inventors have studied an electronic photographic belt including a surface layer of a perfluoropolyether dispersed in a binder resin by using the above-mentioned comb-shaped graft copolymer, which is considered to be environmentally friendly. As a result, the cleaning performance of the surface of the electronic photographic belt decreases over time in some cases. Summary of the invention
[0006] At least one aspect of the present disclosure is to provide an electrophotographic belt that is environmentally friendly and can satisfactorily maintain surface cleaning performance for a long period of time. In addition, another aspect of the present disclosure is to provide an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images.
[0007] According to one aspect of the present disclosure, an electrophotographic belt is provided, which comprises at least a base layer and a surface layer. The surface layer comprises the following A, B, and C:
[0008] A: Compound 1 having a structure represented by structural formula (I) and a structure represented by structural formula (II):
[0009]
[0010] In formula (I),
[0011] R1 represents a linking group, and
[0012] R2 represents a hydrogen atom or a methyl group;
[0013]
[0014] In formula (II),
[0015] R3 represents a hydrogen atom, a methyl group, or a methyl ester group,
[0016] R4 represents a connecting group,
[0017] R5 represents a methyl group or a tert-butyl group, and
[0018] "m" represents an integer from 25 to 100;
[0019] B: Perfluoropolyether;
[0020] C: Binder resin.
[0021] In addition, according to another aspect of the present disclosure, an electronic photographic image forming device is provided, which includes: an image bearing member configured to carry a colorant image; and an intermediate transfer belt configured to carry and convey the colorant image transferred once from the image bearing member to transfer the colorant image to a transfer material for a second time, wherein the intermediate transfer belt is the above-mentioned electronic photographic belt.
[0022] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a schematic cross-sectional view of an image forming apparatus according to an embodiment of the present disclosure.
[0024] Figure 2 is a cross-sectional view for illustrating the configuration of an intermediate transfer belt according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0025] The reason why the satisfactory cleaning performance of the surface of an electrophotographic tape including a surface layer having a perfluoropolyether dispersed in a binder resin is considered to decrease over time by using the above-mentioned comb-shaped graft copolymer, which is considered to be environmentally friendly, is considered to be as follows. That is, it is considered that the ability of the comb-shaped graft copolymer in which the number of continuous carbon atoms in which fluorine atoms are bonded is set to 3 or less to disperse the perfluoropolyether is reduced. Therefore, it is difficult to finely disperse the perfluoropolyether in the binder resin. As a result, a large range of perfluoropolyether is present in the surface layer. The hardness of such a surface layer is low, so its surface is scraped off by repeated cleaning with a cleaning blade. At the same time, it is considered that the perfluoropolyether also disappears from the surface layer, resulting in a decrease in the toner release property of the surface.
[0026] Based on such discussions, further studies were conducted, and as a result, it was found that compounds having a structure represented by the above chemical formula (I) and a structure represented by the above chemical formula (II) have an environmentally friendly structure and are excellent in the ability to disperse perfluoropolyether in a binder resin.
[0027] The exemplary embodiments of the present disclosure are described in detail below with reference to the accompanying drawings. However, specific aspects such as size, material, shape, and relative positional relationship of the structural elements described in the following embodiments may be appropriately changed according to the structure of the device to which the present disclosure is applied and various conditions, and the scope of the present disclosure is not limited to these specific aspects.
[0028] [Image forming apparatus]
[0029] Figure 1 : is a schematic cross-sectional view of an electrophotographic image forming apparatus 100 as an electrophotographic image forming apparatus including an electrophotographic belt according to an embodiment of the present disclosure.
[0030] In the electrophotographic image forming apparatus, image forming units Py, Pm, Pc, and Pk of yellow (Y), magenta (M), cyan (C), and black (K) colors are sequentially arranged along the flat portion of the intermediate transfer belt 7 as an intermediate transfer member in its moving direction. Here, electrophotographic photosensitive members 1Y, 1M, 1C, and 1K, and charging rollers 2Y, 2M, 2C, and 2K are shown. Laser exposure devices 3Y, 3M, 3C, and 3K, developing devices 4Y, 4M, 4C, and 4K, and primary transfer rollers 5Y, 5M, 5C, and 5K are also shown. The basic configuration of each image forming unit is the same, so only the yellow image forming unit Py will be described in detail.
[0031] The yellow image forming unit Py includes a drum-type electrophotographic photosensitive member (hereinafter sometimes referred to as a "photosensitive drum" or a "first image bearing member") 1Y as an image bearing member. The photosensitive drum 1Y is formed by sequentially laminating a charge generating layer, a charge transporting layer, and a surface protective layer on a cylinder made of aluminum serving as a substrate.
[0032] In addition, the yellow image forming unit Py includes a charging roller 2Y serving as a charging unit. The surface of the photosensitive drum 1Y is uniformly charged by applying a charging bias to the charging roller 2Y.
[0033] A laser exposure device 3Y serving as an image exposure unit is disposed above the photosensitive drum 1Y. The laser exposure device 3Y scans and exposes the surface of the uniformly charged photosensitive drum 1Y according to image information, thereby forming an electrostatic latent image of a yellow component on the surface of the photosensitive drum 1Y.
[0034] The electrostatic latent image formed on the photosensitive drum 1Y is developed by the toner used as the developer by the developing device 4Y used as the developing unit. The developing device 4Y includes a developing roller 4Ya used as a developer carrier and a regulating blade 4Yb used as a developer amount regulating member, and contains a yellow toner as the developer. The developing roller 4Ya having the yellow toner supplied thereto is brought into light contact with the photosensitive drum 1Y in the developing section, and is rotated in the forward direction at a speed different from that of the photosensitive drum 1Y. When a developing bias is applied to the developing roller 4Ya, the yellow toner conveyed to the developing section by the developing roller 4Ya adheres to the electrostatic latent image formed on the photosensitive drum 1Y.
[0035] As a result, a visible image (yellow toner image) is formed on the photosensitive drum 1Y.
[0036] The intermediate transfer belt 7 is stretched around a driving roller 71 , a tension roller 72 , and a driven roller 73 , and is in contact with the photosensitive drum 1Y to move (rotationally drive) in the direction of an arrow in the figure.
[0037] The yellow toner image formed on the photosensitive drum (first image bearing member) 1Y reaching the primary transfer portion Ty is primarily transferred onto the intermediate transfer belt 7 by a primary transfer member (primary transfer roller 5Y) arranged to oppose the photosensitive drum 1Y with the intermediate transfer belt 7 interposed therebetween.
[0038] Similarly, the above-mentioned image forming operation is performed in the image forming units Pm, Pc, and Pk of each color of magenta (M), cyan (C), and black (K) as the intermediate transfer belt 7 moves, and the toner images of the four colors of yellow, magenta, cyan, and black are stacked on the intermediate transfer belt 7. The stacked four-color toner images are conveyed as the intermediate transfer belt 7 moves, and are collectively transferred to the transfer material S (hereinafter sometimes referred to as "second image bearing member") conveyed at a predetermined timing by the secondary transfer roller 8 serving as a secondary transfer unit in the secondary transfer portion T'. In such secondary transfer, a transfer voltage of several kilovolts is generally applied to ensure a sufficient transfer rate.
[0039] The transfer material S is supplied to the conveying path from a cassette 12 storing the transfer material S by a pickup roller 13. The transfer material S supplied to the conveying path is conveyed to the secondary transfer portion T' by a conveying roller pair 14 and a registration roller pair 15 in synchronization with the four-color toner image transferred onto the intermediate transfer belt 7.
[0040] The toner image transferred onto the transfer material S is fixed to form, for example, a full-color image by the fixing device 9. The fixing device 9 includes a fixing roller 91 including a heating unit and a pressure roller 92, and fixes the unfixed toner image onto the transfer material S by heating and pressurizing. Thereafter, the transfer material S is delivered to the outside of the apparatus by a conveying roller pair 16, a delivery roller pair 17, and the like.
[0041] The cleaning unit 11 of the intermediate transfer belt 7 is arranged on the downstream side relative to the secondary transfer portion T′ in the driving direction of the intermediate transfer belt 7 and removes transfer residual toner remaining on the intermediate transfer belt 7 without being transferred to the transfer material S in the secondary transfer portion T′.
[0042] As described above, the electro-transfer process of the toner image from the photosensitive member to the intermediate transfer belt and from the intermediate transfer belt to the transfer material is repeated. In addition, when recording on a large amount of transfer materials is repeated, the electro-transfer process is further repeated.
[0043] [Electronic Photographic Tape]
[0044] like Figure 2 As shown in FIG. 1 , the electrophotographic belt 200 according to this embodiment is a laminated body including at least two layers: a base layer 21 and a surface layer 22. The surface layer 22 constitutes the toner carrying surface of the electrophotographic belt 200, that is, the surface 200-1.
[0045] The constitution of the electronic photographic tape according to the present disclosure is not limited to the above-mentioned two-layer laminate. For example, a primer layer (not shown) for improving adhesion, or a stress relaxation layer for suppressing the cracking of the surface layer 22 or an intermediate layer (not shown) for suppressing the exudation of substances can be configured between the base layer 21 and the surface layer 22.
[0046] (Base layer)
[0047] The base layer 21 has a cylindrical shape as a ring roll shape or a strip shape.
[0048] Examples of materials suitable for the base layer 21 include the following materials: polyetheretherketone; polyethylene terephthalate; polybutylene naphthalate; polyester; polyimide; polyamide; polyamideimide; polyacetal; polyphenylene sulfide; and polyvinylidene fluoride.
[0049] The resin for the base layer 21 can be made conductive by adding metal powder, conductive oxide powder, conductive carbon, lithium salt, ionic liquid, or any other conductive compound thereto. In the examples described later, from the viewpoint of achieving excellent conductivity and environmental stability, polyimide added with carbon black is used. However, any combination of other resins and conductivity imparting agents listed can be used.
[0050] The thickness of the base layer 21 is preferably 10 μm or more and 500 μm or less. This is because: when the thickness is less than 10 μm, the mechanical strength will be significantly reduced; and when the thickness is greater than 500 μm, the rigidity will become too strong, and therefore, it may be difficult to use the intermediate transfer belt as an intermediate transfer member.
[0051] (Surface layer)
[0052] The surface layer 22 is formed on the base layer 21, serves as the outermost layer of the intermediate transfer belt according to this embodiment, and contains all of the following A, B, and C:
[0053] A: Compound 1 having a structure represented by the above chemical structural formula (I) and a structure represented by the above chemical structural formula (II) (hereinafter sometimes referred to as "graft copolymer");
[0054] B: Perfluoropolyether (hereinafter sometimes referred to as "PFPE"); and
[0055] C: Binder resin.
[0056] In addition to the above binder resin, PFPE, and graft copolymer, the surface layer 22 may further contain a photoinitiator, a conductive substance, etc.
[0057] <C: Binder resin>
[0058] One or more resins selected from the group consisting of the following can be used as the binder resin: acrylic resin; methacrylic resin; and epoxy resin. The term "one or more resins" includes a mixed resin of resins selected from the above group.
[0059] The binder resin plays the role of a dispersion medium for PEPE. The binder resin is a material for ensuring the adhesion between the surface layer and the base layer 21 and ensuring the mechanical strength of the surface layer itself.
[0060] Among the above-mentioned binder resins, methacrylic resins or acrylic resins are preferably used because PFPE for forming the surface layer 22 of the electrophotographic belt can be dispersed satisfactorily. Methacrylic resins and acrylic resins are hereinafter collectively referred to as "acrylic resins".
[0061] Examples of the polymerizable monomer for forming the acrylic resin include the following (i) and (ii). Commercially available products as coating materials can also be used as the polymerizable monomer.
[0062] (i) at least one acrylate selected from the group consisting of pentaerythritol triacrylate; pentaerythritol tetraacrylate; ditrimethylolpropane tetraacrylate; dipentaerythritol hexaacrylate; alkyl acrylates; benzyl acrylate; phenyl acrylate; ethylene glycol diacrylate; and bisphenol A diacrylate.
[0063] (ii) at least one methacrylate selected from the group consisting of pentaerythritol trimethacrylate; pentaerythritol tetramethacrylate; ditrimethylolpropane tetramethacrylate; dipentaerythritol hexamethacrylate; alkyl methacrylates; benzyl methacrylate; phenyl methacrylate; ethylene glycol dimethacrylate; and bisphenol A dimethacrylate.
[0064] The binder resin preferably has high hardness in consideration of friction with other members such as a photosensitive member and a cleaning blade. Therefore, it is preferred that the acrylic resin has high hardness by using a large amount of a bifunctional or higher crosslinkable monomer.
[0065] In addition, as a method of forming an acrylic resin from such a polymerizable monomer, there is given a method involving adding a photopolymerization initiator and causing polymerization with electron beams and UV light.
[0066] Examples of photopolymerization initiators include the following initiators: photopolymerization initiators that generate free radicals, such as benzophenone, thioxanthone-based initiators, benzyl dimethyl ketal, α-hydroxyketone, α-hydroxyalkylphenone, α-aminoketone, α-aminoalkylphenone, monoacylphosphine oxide, bisacylphosphine oxide, hydroxybenzophenone, aminobenzophenone, titanocene-based initiators, oxime esters, and oxyphenylacetic acid esters.
[0067] The content of the binder resin in the surface layer is preferably set to 20% by mass or more and 70% by mass or less with respect to the total solid content of the surface layer 22, so that the surface layer has excellent strength and the outer surface of the surface layer has excellent toner releasability.
[0068] <B: Perfluoropolyether>
[0069] Perfluoropolyether (hereinafter also referred to as "PFPE") refers to an oligomer or polymer including perfluoroalkylene ether as a repeating unit.
[0070] Examples of the repeating unit of perfluoroalkylene ether include repeating units of perfluoromethylene ether, perfluoroethylene ether, and perfluoropropylene ether. Commercially available products can be used as PFPE. Examples of commercially available products include, but are not limited to, PFPE represented by structural formula (1) (for example, Demnum S-200 and Demnum S-65 (trade names), manufactured by Daikin Industries, Ltd.), PFPE represented by structural formula (2) (for example, Krytox GPL-107, Krytox GPL-106, and Krytox GPL-105 (trade names), manufactured by Chemours Company), PFPE represented by structural formula (3) (for example, Fomblin M60 and Fomblin Z25 (trade names), manufactured by Solvay Specialty Polymers), and PFPE represented by structural formula (4) (for example, Fomblin Y45 and Fomblin Y25 (trade names), manufactured by Solvay Specialty Polymers).
[0071]
[0072] In formula (1), "n" represents a positive number, and "n" represents a number within the range where the kinematic viscosity at 40 °C satisfies 10 mm 2 / s to 300 mm 2 / s.
[0073]
[0074] In formula (2), n' represents a positive number, and n' represents a number within the range where the kinematic viscosity at 40 °C satisfies 5 mm 2 / s to 1,200 mm 2 / s.
[0075]
[0076] In formula (3), n″ and "m" each represent a positive number, m / n″ is a number of 0.5 or more and 2 or less, and n″ + m is a number such that the kinematic viscosity at 40 °C satisfies 10 mm 2 / s to 900 mm 2 / s range.
[0077]
[0078] In formula (4), n″′ and m′ each represent a positive number, m′ / n″′ is a number of 20 or more and 1,000 or less, and n″′ + m′ is a number within the range where the kinematic viscosity at 40 °C satisfies 10 mm 2 / s to 700 mm 2 / s range.
[0079]
[0080] In addition, the PFPE may have a reactive functional group capable of forming a bond or a bond-like state with the binder resin, or a non-reactive functional group capable of forming a bond or a bond-like state with the binder resin. Examples of the reactive functional group include an acrylic group, a methacrylic group, and a siloxy group. In addition, examples of the non-reactive functional group include a hydroxyl group, a trifluoromethyl group, and a methyl group.
[0081] Examples of commercially available products of PFPE having the above reactive functional groups include the following products: "FLUOROLINK MD700", "FLUOROLINK AD1700", and "FLUOROLINK S10" (trade name; manufactured by Solvay S.A.); and "Optool DAC" (trade name; manufactured by Daikin Industries, Ltd.). "MD-500" is a PFPE having a methacrylic group as a functional group, and "FLUOROLINK AD1700" is a PFPE having an acrylic group as a functional group.
[0082] <A: Compound 1>
[0083] Compound 1 according to component A has a structure represented by chemical formula (I) and a structure represented by chemical formula (II). Compound 1 is used as a dispersant for dispersing PFPE in a binder resin. The graft copolymer as compound 1 has both a first unit represented by the following chemical formula (I) and a second unit represented by the following chemical formula (II).
[0084] The first unit is a site with excellent affinity for PEPE, while the second unit has excellent affinity for the binder resin. In addition, the first unit has a perfluoromethyl group as a side chain. It is believed that this compensates for the reduction in the dispersibility of PFPE in the binder resin caused by the introduction of oxygen atoms and setting the number of continuous carbon atoms in the perfluoroalkyl group to 3 or less. As a result, compound 1 according to the present disclosure can make PFPE with low surface free energy more well dispersed in the binder resin.
[0085]
[0086] In formula (II),
[0087] R3 represents a hydrogen atom, a methyl group, or a methyl ester group,
[0088] R4 represents a connecting group,
[0089] R5 represents a methyl group or a tert-butyl group, and
[0090] "m" represents an integer from 25 to 100.
[0091] Examples of the linking group R1 in the chemical structural formula (I) include alkylene groups having 1 to 6 carbon atoms; and groups having 6 or less atoms consisting of carbon atoms, hydrogen atoms, nitrogen atoms, and oxygen atoms and constituting the main chain. Specific examples thereof include alkylene groups having 1 to 6 carbon atoms (e.g., -CH2- or -CH2CH2-), and groups represented by the following structural formula (i), wherein methylene (CH2) and ethylene (CH2CH2) are bonded via a carbamate bond (-OC(=O)NH-). Here, in structural formula (i), the main chain refers to -COCNCC-.
[0092] (i)
[0093] -CH2OC(=O)NHCH2CH2-
[0094] The example of connecting group R4 in chemical structural formula (II) includes a group consisting of carbon atoms, hydrogen atoms, oxygen atoms and sulfur atoms and constituting the number of atoms of the main chain being 9 or less; and a group consisting of carbon atoms, hydrogen atoms, nitrogen atoms, oxygen atoms and sulfur atoms and constituting the number of atoms of the main chain being 9 or less. The specific example of such group is represented by the following structural formulas (ii) to (iv). In structural formula (ii), the main chain refers to -SCCOCCCOC-. In structural formula (iii), the main chain refers to -SCCCNCCOC-. In addition, in structural formula (iv), the main chain refers to -SCCNCCOC-.
[0095] (ii)
[0096] -SCH2C(=O)OCH2CH(OH)CH2OC(=O)-
[0097] (iii)
[0098] -SCH2CH2C(=O)NHCH2CH2OC(=O)-
[0099] (iv)
[0100] -SCH2C(=O)NHCH2CH2OC(=O)-
[0101] The peak top molecular weight of Compound 1 is preferably 20,000 or more and 40,000 or less.
[0102] When the peak top molecular weight falls within the above numerical range, a high steric effect may be exhibited to effectively inhibit aggregation between PFPE molecules.
[0103] Compound 1 can also be defined as an acrylic resin or methacrylic resin having a perfluoroalkyl group having 3 carbon atoms grafted thereon. Such compounds can be obtained by copolymerizing a macromonomer and a monofunctional monomer. Here, the macromonomer is a compound having a high molecular weight compared to ordinary monomers and having a reactive group. A graft copolymer can be obtained by polymerizing a macromonomer having one polymerizable functional group per molecule in such a macromonomer with a monomer having one polymerizable functional group per molecule.
[0104] According to one aspect of the present disclosure, an electrophotographic belt having excellent environmental friendliness and capable of forming satisfactory electrophotographic images for a long period of time can be obtained. In addition, according to one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images can be obtained.
[0105] Example
[0106] The electrophotographic belt according to the present disclosure is described in more detail below by way of non-limiting specific examples.
[0107] <Preparation of Macromonomer>
[0108] <<Macromolecular Monomer No.1>>
[0109] As macromonomer No. 1, a macromonomer having a methyl methacrylate segment (trade name: AA-6; manufactured by Toagosei Co., Ltd., R3 and R5: -CH3, number average molecular weight: 6,000) was prepared.
[0110] <<Macromolecular Monomer No.2>>
[0111] The materials shown in Table 1 below were charged into a glass flask with a reflux condenser, and nitrogen purging was performed while maintaining the temperature in the flask at 15° C. in a water bath.
[0112] Table 1
[0113] Compound Name Blending amount (parts by mass) Tert-Butyl Methacrylate Monomer 10.0 acetone 14.5 Toluene 68.5 2,2′-azobis(isobutyronitrile) 0.5 Thioglycolic acid 0.3
[0114] Thereafter, under a nitrogen atmosphere, the temperature of the water bath was set so that the temperature of the reaction liquid became 85° C., and polymerization reaction was performed for 5 hours. The polymerization reaction was terminated by ice cooling to obtain a solution in which the compound represented by the chemical formula (III) was dissolved.
[0115]
[0116] Then, 60 parts by mass of toluene were added, and triethylamine and hydroquinone monomethyl ether were added at 0.5% by weight and 200 ppm, respectively, relative to the amount of tert-butyl methacrylate monomer added. Glycidyl methacrylate was added in a 10-fold molar amount relative to the acid value of the obtained chemical formula (III), and the reaction was carried out at a temperature of 110°C for 11 hours. The reaction was terminated by water cooling, n-hexane was added, and a precipitate was obtained by centrifugation. Thereafter, the precipitate was dried under reduced pressure for 3 hours at a temperature of 80°C and 1,325Pa or less to obtain a macromonomer No. 2 represented by formula (IV).
[0117]
[0118] <<Macromolecular Monomer No.3>>
[0119] Macromonomer No. 3 represented by formula (V) was produced in the same manner as in Macromonomer No. 2 except that glycidyl methacrylate used in the production of Macromonomer No. 2 was changed to glycidyl acrylate.
[0120]
[0121] <<Macromolecular Monomer No.4>>
[0122] A macromonomer was produced in the same manner as in Macromonomer No. 2 except for the following:
[0123] Changing the tert-butyl methacrylate monomer to methyl methacrylate monomer;
[0124] Change mercaptoacetic acid to 3-mercaptopropionic acid;
[0125] Change glycidyl methacrylate to 2-isocyanatoethyl methacrylate;
[0126] Changing triethylamine to zirconium(IV) acetylacetonate;
[0127] Changing a 10-fold molar amount to a 2-fold molar amount; and
[0128] The reaction at 110° C. for 11 hours was changed to the reaction at 50° C. for 24 hours to obtain macromonomer No. 4 represented by the chemical formula (VI).
[0129]
[0130] <<Macromolecular Monomer No.5>>
[0131] As macromonomer No. 5, POLY (METHYLMETHACRYLATE) MACROMONOMER, ΩVINYL-TERMINATED having a number average molecular weight of 2,800 from Polymer Source, Inc. was prepared.
[0132] <<Macromolecular Monomer No.6>>
[0133] As macromonomer No. 6, POLY (METHYLMETHACRYLATE) MACROMONOMER, ΩVINYL-TERMINATED, a brand with a number average molecular weight of 9,900 from Polymer Source, Inc., was prepared.
[0134] The structures of macromonomers No. 2 to 6 are shown in Table 2. 1 The value of "m" is determined by the peak area ratio of H NMR.
[0135] Table 2
[0136]
[0137] <Preparation of Monomers Each Having a Perfluorinated Structure>
[0138] <<Perfluorinated Monomer No. 1>>
[0139] 1H,1H-Perfluoro(2,5-dimethyl-3,6-dioxanonanoyl)acrylate having a structure represented by the following chemical formula (VIII) is used as perfluorinated structure-containing monomer No. 1. Perfluorinated structure-containing monomer No. 1 is a material providing a structure represented by chemical formula (I). In the structure according to chemical formula (I) formed by perfluorinated structure-containing monomer No. 1, R1 represents a methylene group (CH2), and R2 represents a hydrogen atom (H).
[0140]
[0141] <<Perfluorinated Monomer No. 2>>
[0142] The materials shown in Table 3 below were added to a flask made of glass having a stirrer, a reflux condenser, a nitrogen inlet tube, a constant temperature bath, and a thermometer, and the materials were mixed at a temperature of 20° C. for 30 minutes under a nitrogen atmosphere. Then, the mixture was heated to a temperature of 50° C., and reacted for 24 hours to obtain a perfluorinated structure-containing monomer No. 2 represented by the chemical formula (VII).
[0143] Table 3
[0144]
[0145]
[0146] <Preparation of Graft Copolymer>
[0147] <<Graft Copolymer No.11>>
[0148] The materials shown in Table 4 below were added to a flask made of glass having a stirrer, a reflux condenser, a nitrogen inlet tube, a constant temperature bath, and a thermometer, and the materials were mixed at a temperature of 20°C for 30 minutes under a nitrogen atmosphere. Then, heating was performed so that the temperature of the reaction solution became 85°C to 90°C, followed by reaction for 5 hours. The reaction was terminated by ice cooling, and 1,500 parts by mass of 2-propanol were added to obtain a precipitate. The precipitate was washed with a mixed solvent containing n-butyl acetate and 2-propanol in a ratio of 1:5, and dried at a temperature of 80°C for 3 hours under a reduced pressure state of less than 1,325Pa to obtain a graft copolymer No. 11 as a copolymer of macromonomer No. 1 and monomer No. 1 containing a perfluorinated structure.
[0149] Table 4
[0150] Compound Name Blending amount (parts by mass) Macromonomer No.1 75 Monomer No.1 containing perfluorinated structure 50 1,1′-Azobis(1-acetoxy-1-phenylethane) 0.437 n-Butyl acetate 338
[0151] <<Graft copolymers No. 21, 22, 31, 32, 41, 51, 52, 61, and 62>>
[0152] Graft copolymers Nos. 21, 22, 31, 32, 41, 51, 52, 61, and 62 were prepared in the same manner as in graft copolymer No. 11, except that the kind of the macromonomer, the kind of the perfluorinated structure-containing monomer, and the blending amount of 1,1′-azobis(1-acetoxy-1-phenylethane) were set as shown in Table 5.
[0153] Table 5
[0154]
[0155] <<Graft Copolymer No.90>>
[0156] A graft copolymer was produced in the same manner as in graft copolymer No. 11 except that perfluorinated structure-containing monomer No. 1 was changed to 2,2,3,3,4,4,4-heptafluorobutyl acrylate having a structure represented by the following chemical formula (IX). Thus, graft copolymer No. 90 was obtained.
[0157]
[0158] <Measurement of Peak Top Molecular Weight>
[0159] The peak top molecular weight of each obtained graft copolymer is shown in Table 6. After the measurement sample was dissolved in tetrahydrofuran (hereinafter sometimes referred to as "THF") to prepare a solution with a concentration of 0.2 mass%, the peak top molecular weight was measured with a gel permeation chromatography (hereinafter sometimes referred to as "GPC") apparatus GPC-104 (from Shodex). The molecular weight was measured at a column temperature of 40°C and a THF flow rate of 1.0 mL / min by connecting "GPC KF-603" and "GPC KF-604" from Shodex one by one. The weight average molecular weight (Mw) of the sample was calculated from a calibration curve prepared in advance using a polystyrene standard substance (SM-105 from Shodex) having a known molecular weight.
[0160] Table 6
[0161]
[0162] [Example 1]
[0163] The materials shown in Table 7 below were mixed using a homogenizer to obtain Coating A.
[0164] Table 7
[0165]
[0166] On the outer peripheral surface of an endless electrophotographic belt made of a polyimide resin in which carbon black is dispersed, which is to be mounted as an intermediate transfer belt in a full-color multifunction peripheral (trade name: imageRUNNERADVANCEC5051; manufactured by Canon Inc.), a coating film of coating material A is applied so that the dry thickness is 6 μm. Then, the resultant is dried at a temperature of 70° C. for 3 minutes. Thereafter, the peak illuminance at a wavelength of 365 nm is 200 mW / cm 2 , and the integrated light intensity is 2J / cm 2 The coating film was cured by irradiation with UV light using a high pressure mercury lamp under the conditions of , to form a surface layer. Thus, an electrophotographic belt No. 1 was obtained. The obtained electrophotographic belt was subjected to the following evaluation 1 and evaluation 2.
[0167] <Evaluation 1: Measurement of Hardness of Electrophotographic Belt>
[0168] The hardness of the electrophotographic belt was measured by a nanoindentation method. Specifically, a microhardness tester (trade name: PICODENTOR HM500; manufactured by Fischer Instruments) was used and a Vickers indenter was used as an indenter to determine the indentation hardness by performing a nanoindentation test at an indentation depth of 100 nm to 200 nm.
[0169] <Evaluation 2: Evaluation of electrophotographic characteristics>
[0170] An electrophotographic image was formed using each of the electrophotographic belts obtained in Examples 1 to 11 and Comparative Example 1, and the resulting electrophotographic images were evaluated.
[0171] That is, an electrophotographic belt was mounted as an intermediate transfer belt to a full-color multifunction peripheral (trade name: imageRUNNERADVANCE C5760F; manufactured by Canon Inc.), and 30,000 sheets of electrophotographic images were continuously formed under the following conditions. Regarding the formation of the electrophotographic images, images were formed on 30,000 sheets of paper by repeating the following cycle 300 times: cyan (C), magenta (M), yellow (Y), and black (K) were formed on 97 sheets of paper. The toner load on the surface of each of the electrophotographic belts was 0.4 mg / cm 2 , and a solid image with an image ratio of 100%, and then the CMYK toners on the surface of the electronic photographic belt are formed on 3 sheets with a loading amount of 0 mg / cm 2 The electronic photographic image was formed in an environment with a temperature of 30°C and a relative humidity of 80%. In addition, the paper used was "GF-C081" (A3 size, basis weight: 81.4 g / m 2 , thickness: 97 μm, whiteness: about 100%, manufactured by Canon Inc.).
[0172] Then, visual observation showed that the loading was 0 mg / cm 2 A white solid image is formed on the electrophotographic belt surface, and then it is identified whether a streak-like image caused by poor cleaning of the electrophotographic belt surface is formed on the white solid image to which the toner is not intended to be transferred.
[0173] Then, when the streak-like image is observed, the cleaning blade abutting against the surface of the electrophotographic belt is visually observed, and then it is identified whether the toner (transfer residual toner) not secondarily transferred to the surface of the electrophotographic belt is cleaned by the cleaning blade. Then, when it can be identified that the transfer residual toner is not cleaned by the cleaning blade, it is judged that the streak-like image is caused by poor cleaning of the surface of the electrophotographic belt. In this evaluation, the evaluation is performed by the following criteria based on the results of the above observation.
[0174] Rank A: No streak-like image caused by poor cleaning of the surface of the electrophotographic belt was found on the white solid image.
[0175] Rank B: A streak-like image caused by poor cleaning of the surface of the electrophotographic belt was found on the white solid image.
[0176] [Examples 2 to 10]
[0177] A coating material was produced in the same manner as in Example 1 except that the graft copolymer No. 11 was changed as shown in Table 8, and electrophotographic belts Nos. 2 to 10 were obtained. The obtained electrophotographic belts were each subjected to the above-mentioned Evaluation 1 and Evaluation 2.
[0178] Table 8
[0179] Electronic Photographic Tape No. Graft copolymer No. Example 1 1 11 Example 2 2 21 Example 3 3 22 Example 4 4 31 Example 5 5 32 Example 6 6 41 Example 7 7 51 Example 8 8 52 Example 9 9 61 Example 10 10 62
[0180] [Example 11]
[0181] 95 parts by mass of pentaerythritol triacrylate was changed to 40 parts by mass of bisphenol A-type epoxy acrylate (EBECRYL 600, manufactured by Daicel-Allnex Ltd.) and 55 parts by mass of pentaerythritol triacrylate. Except for this change, a coating was produced in the same manner as in Example 2, and an electrophotographic tape No. 11 was obtained. The obtained electrophotographic tape was subjected to the above-mentioned Evaluation 1 and Evaluation 2.
[0182] [Comparative Example 1]
[0183] A coating was produced in the same manner as in Example 1 except that the graft copolymer No. 11 was changed to the graft copolymer No. 90, and an electrophotographic belt No. 90 was obtained. The obtained electrophotographic belt No. 90 was subjected to the above-mentioned Evaluation 1 and Evaluation 2. In Evaluation 2, a streak-like image caused by poor cleaning was generated in the white solid image formed in the 100th cycle, and thus the image formation was stopped after the completion of 200 cycles.
[0184] The evaluation results of Examples 1 to 11 and Comparative Example 1 are shown in Table 9.
[0185] Table 9
[0186]
[0187] The results of Evaluation 1 and Evaluation 2 of the electrophotographic tape No. 90 according to Comparative Example 1 are considered to be due to the low dispersibility of PFPE in the binder resin caused by the difference between the surface free energy of the comb-shaped graft copolymer No. 90 and the surface free energy of the comb-shaped graft copolymers used in the examples. In the electrophotographic tape No. 90, the PFPE in the surface layer is not finely dispersed, and therefore, as is apparent from the result of Evaluation 1, the hardness of the surface layer is reduced. As a result, it is considered that the surface layer is worn away by repeatedly cleaning the surface of the electrophotographic tape, and therefore, the PFPE in the surface layer disappears with the wear. For this reason, it is presumed that the cleaning performance of the surface of the electrophotographic tape is reduced over time.
[0188] Meanwhile, in the electrophotographic belt according to each embodiment, the PFPE in the surface layer is finely dispersed, and therefore, the hardness of the surface layer is maintained at a high level. Therefore, even when the surface of the electrophotographic belt is repeatedly cleaned, the surface layer is hardly worn. In addition, since the PFPE is finely dispersed, even when the surface layer is worn, the domains of the PFPE exist in a substantially uniform manner in the thickness direction of the surface layer. For this reason, it is considered that the cleaning performance of the surface of the electrophotographic belt is hardly reduced even by repeated use.
[0189] In order to show the difference in surface free energy between the graft copolymers of Examples and Comparative Examples, the n-hexadecane contact angles of the thin film of graft copolymer No. 21 and the thin film of graft copolymer No. 90 are shown in Table 10.
[0190] Table 10
[0191] n-Hexadecane contact angle (°) Graft copolymer No.21 71 Graft copolymer No.90 53
[0192] Table 11 shows a list of CAS numbers and manufacturer names of materials cited by common names among the materials used in Examples.
[0193] Table 11
[0194]
[0195] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. An electrophotographic tape, characterized in that It includes at least: Grassroots; and Contains the following A, B, and C surface layers: A: Compound 1 having a structure represented by structural formula (I) and a structure represented by structural formula (II): (I) In formula (I), R1 represents a linking group, and R2 represents a hydrogen atom or a methyl group; (II) In formula (II), R3 represents a hydrogen atom, a methyl group, or a methyl ester group, R4 represents a connecting group, R5 represents a methyl group or a tert-butyl group, and "m" represents an integer from 25 to 100; B: Perfluoropolyether; C: Binder resin.
2. The electrophotographic tape according to claim 1, wherein the linking group R1 is an alkylene group having 1 to 6 carbon atoms; or A group composed of carbon atoms, hydrogen atoms, nitrogen atoms, and oxygen atoms, with the number of atoms constituting the main chain being 6 or less.
3. The electrophotographic tape according to claim 1 or 2, wherein the linking group R1 is a group represented by the following structural formula (i), (i) -CH2OC(=O)NHCH2CH2-.
4. The electrophotographic tape according to claim 1, wherein the linking group R4 is A group consisting of carbon atoms, hydrogen atoms, oxygen atoms, and sulfur atoms, with the number of atoms constituting the main chain being 9 or less; or A group composed of carbon atoms, hydrogen atoms, nitrogen atoms, oxygen atoms, and sulfur atoms, with 9 or less atoms constituting the main chain.
5. The electrophotographic tape according to claim 1 or 4, wherein the linking group R4 is any one selected from the group consisting of the following structural formulas (ii) to (iv), (ii) -SCH2C(=O)OCH2CH(OH)CH2OC(=O)- (iii) -SCH2CH2C(=O)NHCH2CH2OC(=O)- (iv) -SCH2C(=O)NHCH2CH2OC(=O)-.
6. The electrophotographic belt according to claim 1 or 2, wherein the binder resin is one or more resins selected from the group consisting of: an acrylic resin; a methacrylic resin; and an epoxy resin. 7 . The electrophotographic belt according to claim 1 , wherein the peak top molecular weight of the compound 1 is 20,000 or more and 40,000 or less.
8. An electrophotographic image forming device, characterized in that: It includes: an image bearing member configured to bear a toner image; and an intermediate transfer belt configured to carry and convey the toner image primarily transferred from the image bearing member to secondarily transfer the toner image onto a transfer material, The intermediate transfer belt is an electrophotographic belt according to any one of claims 1 to 7.
Citation Information
Patent Citations
Electrophotographic belt and electrophotographic image formation device
JP2019012265A
Electrophotographic member, intermediate transfer member, image forming apparatus, and method for manufacturing electrophotographic member
CN103163748A
Image bearing member for electrophotography
US20190243261A1